Purchase order for supply of tiles for classroom of Brac University new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and A & H Gallery, Akij Ceramics Ltd. as well as X Ceramics Limited for supply of tiles for classroom for Brac University new campus project.